2007
DOI: 10.1016/j.str.2007.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Insights into Equilibrium Dynamics of Proteins from Comparison of NMR and X-Ray Data with Computational Predictions

Abstract: For a representative set of 64 nonhomologous proteins, each containing a structure solved by NMR and X-ray crystallography, we analyzed the variations in atomic coordinates between NMR models, the temperature (B) factors measured by X-ray crystallography, and the fluctuation dynamics predicted by the Gaussian network model (GNM). The NMR and X-ray data exhibited a correlation of 0.49. The GNM results, on the other hand, yielded a correlation of 0.59 with X-ray data and a distinctively better correlation (0.75)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
143
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(155 citation statements)
references
References 41 publications
11
143
0
1
Order By: Relevance
“…66 It is also possible to use a set of experimental structures in different liganded complexes (if they are available) to compute the binding induced dynamics. [67][68][69][70] The recent study of Bakan and Bahar has shown that ENM predicted modes are very well correlated with the principal components of the conformational change for a large set of different liganded experimental structures of a given protein. 71 We have repeated the same analysis for our test protein: PDZ domain.…”
Section: Elastic Network Model and Generating New Conformations Usingmentioning
confidence: 96%
“…66 It is also possible to use a set of experimental structures in different liganded complexes (if they are available) to compute the binding induced dynamics. [67][68][69][70] The recent study of Bakan and Bahar has shown that ENM predicted modes are very well correlated with the principal components of the conformational change for a large set of different liganded experimental structures of a given protein. 71 We have repeated the same analysis for our test protein: PDZ domain.…”
Section: Elastic Network Model and Generating New Conformations Usingmentioning
confidence: 96%
“…The only information required to implement the method is the knowledge of the native structure obtained from the PDB (26). The GNM has been widely applied because it yields results in agreement with X-ray spectroscopy and NMR experiments (17,27). In order to study diffusion, we transform all springs in the GNM into edges creating a three-dimensional network of nodes.…”
Section: Diffusion On the Protein Foldmentioning
confidence: 99%
“…We then explore the use of these two reference structures to support the evaluation of the significance of the few apparent differences between the experimental NMR and crystal structures. While systematic comparisons of crystal structures and NMR structures have been carried out for many years (see, for example, Billeter et al, 1989;Braun et al, 1989Braun et al, , 1992Hyberts et al, 1992;Yang et al, 2007), owing to the advancement of the two methodologies and the automated methods that can reduce human error or bias, we can now focus on more subtle differences between the NMR and crystal structures that might in some instances also relate to the biological function. The identification of such locally variable sites is guided by a search for sequence locations with high B values in the crystal structure or/and high variation within the bundle of 20 NMR conformers.…”
Section: Strategy For Structure Comparisonsmentioning
confidence: 99%